Digital Branding Strategy through Instagram in Shaping the Brand Image of Giggle's Wedding Organizer - Elga Elgia Eprin; Siti Khumayah; Aghnia Dian Lestari (PT. Caesarindo Triloka Persada, 2026)
The use of Instagram as a marketing communication medium is increasingly playing an important role in the formation of brand image, especially in the creative services industry such as wedding organizers. Instagram's visual-focused character makes it a strategic space to display brand identity and build audience perception. This study aims to examine how the visual representation of Giggle's Wedding Organizer's Instagram content is displayed, how the brand image is formed, and how the audience interprets the content. This study uses a qualitative approach. Data collection was carried out through interviews and observations on @giggleweddingorganizer_'s Instagram account. The results show that consistent management of visual content, including wedding documentation, uniformity of visual style, and the use of supporting narratives, plays a role in shaping the brand image of Giggle's Wedding Organizer as a professional and trusted service provider. In addition, audiences actively interpret content based on visual experience and preferences, so that meaning helps strengthen the brand's image. This study concludes that the formation of brand image through Instagram is the result of the interaction between the visual representation strategy carried out by the brand and the audience interpretation process of the content presented.